Insulin stimulates atypical protein kinase C‐mediated phosphorylation of the neuronal adaptor FE65 to potentiate neurite outgrowth by activating ARF6‐Rac1 signaling. Issue 11 (17th October 2022) - Chau, Dennis Dik‐Long; Li, Wen; Chan, Wai Wa Ray; Sun, Jacquelyne Ka‐Li; Zhai, Yuqi; Chow, Hei‐Man; Lau, Kwok‐Fai
Abstract: Neurite outgrowth is a fundamental process in neurons that produces extensions and, consequently, neural connectivity. Neurite damage and atrophy are observed in various brain injuries and disorders. Understanding the intrinsic pathways of neurite outgrowth is essential for developing strategies to stimulate neurite regeneration. Insulin is a pivotal hormone in the regulation of glucose homeostasis. There is increasing evidence for the neurotrophic functions of insulin, including the induction of neurite outgrowth. However, the associated mechanism remains elusive. Here, we demonstrate that insulin potentiates neurite outgrowth mediated by the small GTPases ADP‐ribosylation factor 6 (ARF6) and Ras‐related C3 botulinum toxin substrate 1 (Rac1) through the neuronal adaptor FE65. Moreover, insulin enhances atypical protein kinase Cι/λ (PKCι/λ) activation and FE65 phosphorylation at serine 459 (S459) in neurons and mouse brains. In vitro and cellular assays show that PKCι/λ phosphorylated FE65 at S459. Consistently, insulin potentiates FE65 S459 phosphorylation only in the presence of PKCι/λ. Phosphomimetic studies show that an FE65 S459E mutant potently activates ARF6, Rac1, and neurite outgrowth. Notably, this phosphomimetic mutation enhances the FE65‐ARF6 interaction, a process that promotes ARF6‐Rac1‐mediated neurite outgrowth. Likewise, insulin treatment and PKCι/λ overexpression potentiate the FE65–ARF6 interaction. Conversely, PKCι/λ knockdown suppresses the stimulatory effect of FE65 on ARF6‐Rac1‐mediated neurite outgrowth. The effect of insulin on neurite outgrowth is also markedly attenuated in PKCι/λ knockdown neurons, in the presence and absence of FE65. Our findings reveal a novel mechanism linking insulin with ARF6‐Rac1‐dependent neurite extension through the PKCι/λ‐mediated phosphorylation of FE65.